Overcoming obstacles to peace : local factors in nation-building - Dobbins, James (2013)
This volume analyzes the impediments that local conditions pose to successful outcomes of nation-building interventions in conflict-affected areas. Previous RAND studies of nation-building focused on external interveners' activities. This volume shifts the focus to internal circumstances, first identifying the conditions that gave rise to conflicts or threatened to perpetuate them, and then determining how external and local actors were able to modify or work around them to promote enduring peace. ...